IMPLEMENTATION OF TPS LEARNING MODELS WITH PROBLEM POSING TO TRAIN CREATIVE THINKING ON ACID-BASE - Wisma Imelda Setyowati; Rusmini Rusmini (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
The research aims to be aware of the implementation of the TPS learning model with problem posing strategies on acid-base, student activity, creative thinking skills, completeness of learning outcomes, and responses of the learning model used. Use one group pretest-posttest research design and was applied to 54 high school students in class XI. The average percentage obtained by the feasibility of the learning model to 91.67% at the first meeting and to 98.60% at second meeting which both of them fall into the excellent category. The relevant activities result at the first meeting to 94,69% and irrelevant by 5,31% while activities of relevant at second meeting to 93,09% and irrelevant by 6,91%,, creative thinking skills increased by a percentage of 40.74% for the high category, 44.44% medium category, and 14.82% low category, for classical completeness learning outcomes by 88.89 %, and students' responses were 95.60% positive while 4.40% for negative responses.